Long Distance Dual SpO2 Monitoring System for Premature Babies Using Bluetooth Communication - Priyambada Cahya Nugraha; Muhammad Ridha Mak'ruf; Lusiana; Sari Luthfiyah; Wahyu Caesarendra (Department of Electromedical Engineering, POLTEKKES KEMENKES SURABAYA and IKATEMI, 2021)
Monitoring the baby's health status is very important, especially for babies born prematurely. Oxygen saturation levels in newborns are very important to know because when the oxygen saturation levels in newborns are low, it is necessary to watch out for hemodynamic abnormalities in the baby. Measurement of oxygen saturation levels in newborns can help detect congenital abnormalities in infants early. This study aims to design an equipment system to continuously monitor the condition of oxygen saturation in newborns. Where in this discussion a monitoring tool is used to monitor 2 premature babies in a baby incubator simultaneously using a Neonatal Fingertip sensor. The system will display the oxygen saturation (SpO2) value and signal. Monitoring on this tool is done wirelessly using the HC-05. Based on the results of tests and measurements in 5 different patients with a pulse oximeter comparison, the difference value of 1% in each patient's results was obtained. The results of this study will greatly help facilitate the work of paramedics in monitoring the vital conditions of newborn babies.